Navigating Limitations and Clinical Challenges in Indonesian Tertiary Trauma Center for Penetrating Brain Injury: A Case Report and Literature Review - Apriawan, Tedy; Al Fauzi, Asra; Suroto, Nur Setiawan; Armando, Alivery Raihanada; Pratama, Mohammad Rizky (Asian Journal of Neurosurgery, 2025)
Penetrating brain injury (PBI) accompanied by vascular injury is a severe trauma, often resulting in high mortality, particularly in low- and middle-income countries where many aspects of health care facilities are limited. Effective management of PBI requires efficient prehospital management, followed with advanced neurosurgical equipment, and continuous neurocritical monitoring. Delays in treatment due to inadequate transport infrastructure, scarce facilities, lack of specialized personnel, and inadequate transport infrastructure significantly elevate mortality rates. Neurointensive monitoring with radiological modalities plays significant role in detecting secondary processes in PBI, nevertheless facing significant limitations due to restricted access and resource allocation under national health insurance limit in clinical practice. Furthermore, undetected vascular complications could contribute to the high mortality observed in these environments. This case highlights the dilemmas in the neurocritical care of PBI as well as the need for improved health care policies for better health care.
Keywords: case report; penetrating brain injury; intraventricular hemorrhage; mortality rate; intensive care unit; health insurance